1963
DOI: 10.1126/science.141.3581.630
|View full text |Cite
|
Sign up to set email alerts
|

Eyeball Retraction: Classical Conditioning and Extinction in the Albino Rabbit

Abstract: A comparison of the percentage-performance curve of a classical conditioning group with those of three control groups provided unequivocal evidence of successful conditioning of the retractor bulbi response to an auditory conditioned stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The eyeblink reflex in the rabbit is a coordinated response involving simultaneous and perfectly correlated external eyelid closure, eyeball retraction, and resulting passive extension of the nictitating membrane (NM; Gormezano et al 1962;Schneiderman et al 1962;Deaux and Gormezano 1963;McCormick et al 1982c). It is but one adaptive response with several components.…”
Section: The Ur Pathwaysmentioning
confidence: 99%
“…The eyeblink reflex in the rabbit is a coordinated response involving simultaneous and perfectly correlated external eyelid closure, eyeball retraction, and resulting passive extension of the nictitating membrane (NM; Gormezano et al 1962;Schneiderman et al 1962;Deaux and Gormezano 1963;McCormick et al 1982c). It is but one adaptive response with several components.…”
Section: The Ur Pathwaysmentioning
confidence: 99%
“…It is controlled via the oculomotor nuclei, which are also involved in eyelid movement, a response that has been extensively studied using classical conditioning techniques. Although eye movement has occasionally been studied as a classically conditioned response (Deaux and Gormezano, 1963;Zikmund, 1964), operant conditioning of eye movement has not previously been reported. Operant conditioning of this response is of interest, particularly if low rates can be brought under control by a schedule, such as differential reinforcement of low rate (DRL), (Skinner and Morse, 1958;Wilson and Keller, 1953), in which only those responses which terminate interresponse times longer than some particular value (the DRL value) effects of different rates of wakeful eye movement on rapid eye movements occurring during subsequent, low-voltage, fast-wave electroencephalographic (EEG) sleep (Meier and Berger, 1965); these effects will be reported elsewhere.…”
mentioning
confidence: 99%
“…Levinthal (1973) proposed that, for the eyelid response and the nictitating membrane response, an eye-widening OR might act antagonistically to the respective CR, during the portion of the CS-US interval in which an OR would occur. Recent studies (Cegavske, Thompson, Patterson, & Gormezano, 1976;Marek, McMaster, Gormezano, & Harvey, 1984), however, have reevaluated what was thought to be a close interconnection between the nictitating membrane and eyelid (Deaux & Gormezano, 1963;Last, 1961). The recent studies have concluded, on the basis of musculature and neural innervation, that the nictitatingmembrane response is uniphasic and separate from that of the outer eyelids.…”
Section: Resultsmentioning
confidence: 99%